ANALISIS SEMIOTIKA FILM MY STUPID BOSS - Rhicard Yulio Resmardi; Dian Esti Nurati, Siswanta (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2017)
ANALISIS SEMIOTIKA FILM MY STUPID BOSS Oleh:Rhicard Yulio ResmardiDian Esti NuratiSiswanta ABSTRACT This research was the excavation of the meaning of the message contained in a few selected scene in the movie "My Stupid Boss. The title of this research is the analysis of Semiotics of movies My Stupid Boss. A good composition is definitely capable of supporting tersampainya the message contained in the film. Researchers interested in representing the meaning of the message contained in the selected scene movie My Stupid Boss.The current study qualitative descriptive nature. So that data is not given in the form of figures or numbers. As a deskritif, then the research this research just presented the situation or discourse, not looking for a relationship, and does not test the hypothesis or make predictions. So data are specifically delegated substantive categories which are then interpreted by references, citations, and references.This research was the excavation of the meaning of the message contained in a few selected scene in the movie "My Stupid Boss. The title of this research is the analysis of Semiotikan Film My Stupid Boss. A good composition is definitely capable of supporting tersampainya the message contained in the film. Researchers interested in representing the meaning of the message contained in the selected scene movie My Stupid Boss, after that the researchers infer the message into one unity.The theory used in this research is semiotics Roland Barthes by analyzing the techniques in the field of cinematography through photography, and then in the maknai with konotatif in denotative and myth. Semiotics Roland Barthes has two stages, the first of the significance of denoted meaning i.e. the most real of a sign, and the second stage is the connotation that would later on describe the meaning of his message.Based on the analysis that has been done on the film My Stupid Bossdapat in pull the conclusion that some of the konotatif in denotative signs in get in the film follows the story lines are interconnected and provide the moral meaning of, please help, honesty and keiklasan. If seen in the film there is a sign – the sign of a negative nature fisted, arrogant, selfish, and a sign of moral rectitude, awareness, mutual help and please keiklasan, essentially the beginning of the story the film director wants to show case negative first and then at the end of the story the Director give it positive behaviors that mark through the scenes of the children of the orphanage. Keywords: Semiotics, In Denotative, Konotatif, My Stupid Boss